All‐optical logic inverter for large‐scale integration in silicon photonic circuits. Issue 5 (1st October 2020) - Datta, Tanmoy; Sen, Mrinal
Abstract : A new device architecture of an all‐optical logic inverter (AOLI) has been proposed in this study. The AOLI functions based on stimulated Raman scattering (SRS) in silicon nanocrystal embedded slotted photonic crystal waveguide (SPCW). The operating power and footprint size of the proposed device have significantly been scaled down to ∼1.5 mW and ∼ 8.5 × 42 μ m 2, respectively, by combining the benefits of giant SRS gain of silicon nanocrystal and ultra‐high spatio‐temporal confinement of the SPCW. Cascadability of the proposed AOLI has been investigated using the maximum product criterion of the noise margin. The successful operation of the AOLI has been demonstrated for the repetition rate of the pulses as high as 100 Gbps. Finally, tolerance of performance of the design under different types of fabrication imperfections has also been calculated to establish its sustainability in a practical scenario.